Kirchnerism and Lulism in construction of an identity in Defence and International Security between Argentina and Brazil - Soares, Samuel Alves [UNESP]; Milani, Livia Peres [UNESP] (Univ Nacl La Plata, Fac Law & Science, 2016)
The governments of Luiz Inacio Lula da Silva and Nestor Kirchner have sought to promote changes in public policies, in the form of international integration and design of regionalism. The pursuit of changes occurred in different ways, and the Lulism was more conciliatory, while kirchnerismo adopted a more confrontational format. In view of this, the objective of this article is to understand the process of building an identity between the two countries which the analysis based on the actions of Foreign Policy and civil-military relations, focusing on the area of Defense and International Security. We conclude that, despite convergence of worldviews, resulting from changes caused by such governments, the formation of an identity in this area progressed, albeit with low depth, among other grounds on different guidelines on the use of armed forces.
Keywords: Identity Defense and International Security; Regionalism; Defense Cooperation Foreign Policy; Brazil-Argentina relations